Measurement of W±γ differential cross sections in proton-proton collisions at √s=13 TeV and effective field theory constraints - Tumasyan, Armen; Adam, Wolfgang; Andrejkovic, Janik Walter; Borshch, Vladislav; Ivanchenko, Vladimir; Tcherniaev, Evgueni (Physical Review D)
Differential cross section measurements of W(+/-)y production in proton-proton collisions at root s = 13 TeV are presented. The data set used in this study was collected with the CMS detector at the CERN LHC in 2016-2018 with an integrated luminosity of 138 fb(-1). Candidate events containing an electron or muon, a photon, and missing transverse momentum are selected. The measurements are compared with standard model predictions computed at next-to-leading and next-to-next-to-leading orders in perturbative quantum chromodynamics. Constraints on the presence of TeV-scale new physics affecting the WW gamma vertex are determined within an effective field theory framework, focusing on the O-3w operator. A simultaneous measurement of the photon transverse momentum and the azimuthal angle of the charged lepton in a special reference frame is performed. This two-dimensional approach provides up to a factor of ten more sensitivity to the interference between the standard model and the O-3w contribution than using the transverse momentum alone.